Database systems design, implementation, and management - Coronel, Carlos; Morris, Steven (Cengage Learning, 2015)
Gives students a foundation in database design and implementation. Filled with visual aids such as diagrams, illustrations, and tables, this book provides coverage of database design, demonstrating that the key to successful database implementation is in proper design of databases to fit within a larger strategic view of the data environment